Comparison of training and match load between metabolic and running speed metrics of professional Spanish soccer players by playing position - Guerrero-Calderón, B.; Alfonso Morcillo, J.; Chena, M.; Castillo-Rodríguez, A. (Biology of Sport, 2022)
The aims of this study were to compare the training and match load of professional soccer players according to the playing position, and analyse the relationship between the metabolic and running speed metrics. Thirty professional male soccer players belonging to a Spanish First Division team were analysed using global positioning system devices (GPEXE Pro 18.18 Hz) during training and competition (n = 36 training weeks and n = 41 matches). The results showed significant differences between positions on match day; central midfielders covered higher total distance and low- and medium-speed running distance (moderate to large effect size) than central defenders, external defenders and forwards; forwards performed more metabolic power events than central defenders, central midfielders and wide midfielders; and central defenders showed the lowest very-high-speed running. Different patterns were observed in training. Furthermore, the equivalent1distance index showed a strong correlation with accelerations and decelerations events. The main findings were that the physical responses found in training did not correspond with match demands by position; both metabolic and traditional approaches should be used together for load monitoring in professional soccer players; and finally, metabolic power events and the equivalent-distance index seem to be variables that help to differentiate more clearly the characteristics of the player, taking into account their playing position.